SalonOvations' guide to aromatherapy - Hess, Shelley M. (Milady Publishing Co., 1996)
Here's the first and only book on aromatherapy solely devoted to the beauty industry. Designed for all skill levels, it offers a full spectrum of non-product specific recipes, definitions, and tried-and-true techniques in the hair, skin, and nail products commonly used by cosmetologists and helps you determine which mixtures of various elements are the most effective for certain kinds of therapies